2020
DOI: 10.1021/acsomega.0c04917
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly Green Synthesis of the ZnO-Doped CuO@Alg Bionanocomposite for Efficient Oxidative Degradation of p-Nitrophenol

Abstract: In the present study, ecofriendly green synthesized ZnO/CuO nanorods were prepared by using the stabilizing and reducing characteristics of the alginate biopolymer. The bionanocomposite (BNC) material was characterized by various sophisticated analytical tools such as Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy− energy dispersive X-ray spectroscopy, transmission electron microscopy, UV−visible spectroscopy, differential scanning calorimetry, and the Brunauer−Emmett−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…In the presence of ZnO the new interactions between –OH moieties and nanoparticles’ surface, induce small shifts in the peak position [ 87 ]. Such shifts were previously reported for alginate–ZnO interactions [ 88 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In the presence of ZnO the new interactions between –OH moieties and nanoparticles’ surface, induce small shifts in the peak position [ 87 ]. Such shifts were previously reported for alginate–ZnO interactions [ 88 ].…”
Section: Resultssupporting
confidence: 84%
“…In the presence of ZnO the new interactions between -OH moieties and nanoparticles' surface, induce small shifts in the peak position [87]. Such shifts were previously reported for alginate-ZnO interactions [88]. The peak from 2921 cm −1 , attributed to C-H symmetric vibration, remains largely unchanged.…”
Section: Ftir Spectroscopysupporting
confidence: 66%
“…Nowadays, the photooxidation of organic pollutants based on TiO 2 nanomaterials is still gain huge attention. Several recent studies have shown the effective role of TiO 2 in oxidizing and mineralizing a wide range of hazardous organic contaminants [118,119], such as alcohol [120,121], organic acids [122], aromatic hydrocarbons [104], phenols [123], dyes [124], pharmaceuticals [125,126], and pesticides [126]. The photocatalytic oxidation of organic pollutants proceeds either by the direct attack of the photogenerated holes or via the attack of the highly reactive hydroxyl radicals generated at the surface of the photocatalyst [110].…”
Section: Methods Of Treatmentmentioning
confidence: 99%
“…The degradation was achieved in 137 min, followed pseudo rst-order kinetics for which cOH oxidative radicals were responsible for achieving the target with 98.32% efficiency. 40 Therefore, this research focuses on two main objectives. The rst is to synthesize ZnO nanostructures with different loading of alginate polymer and study its texture, structure, and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation was achieved in 137 min, followed pseudo first-order kinetics for which ˙OH oxidative radicals were responsible for achieving the target with 98.32% efficiency. 40 …”
Section: Introductionmentioning
confidence: 99%